Identification of Longitudinal Sensory Subtypes in Typical Development and Autism Spectrum Development Using Growth Mixture Modelling. (October 2020) - Dwyer, Patrick; Saron, Clifford D.; Rivera, Susan M.
Highlights: Autistic individuals vary widely in their levels of sensory features and challenges. Sensory features in autism generally remain roughly stable in early childhood. In a small subgroup, sensory features and challenges increase over time. A subgroup with more sensory features and challenges also exhibits elevated anxiety. Abstract: Background: Prior longitudinal investigations of trajectories of sensory features in Autism Spectrum Development (ASD) have not explored heterogeneity. The present study explores initial levels and trajectories of sensory features in ASD as well as, for comparison, typical development. Method: Growth mixture modelling was used to explore classes of autistic and typically-developing participants based on caregiver-reported total sensory behaviours on the Short Sensory Profile (SSP) at two time points, when children were aged 2-5 and 4-10 years of age, respectively. Results: Three classes are described: a mixed class of autistic and typically-developing participants with few problematic sensory behaviours ("Stable Mild"), a mostly-autistic class with more problematic sensory features ("Stable Intense"), and a small class of autistic participants whose sensory features reportedly worsened ("Increasingly Intense"). Autistic participants in the Stable Intense class exhibited high anxiety, while autistic participants in the Increasingly Intense class appeared to obtain high scores on cognitive assessments. Conclusions: The heterogeneity of sensory features and challenges found in the present study may suggest that practitioners should conduct individualized assessments of sensory features in ASD. Furthermore, practitioners should be aware of links between sensory features and anxiety in ASD, which may imply that sensory accommodations and supports could protect against anxiety. Finally, the worsening of sensory features over time in the Increasingly Intense subgroup may indicate a need for continued monitoring of changes in sensory features, perhaps especially as sensory environments change during periods of transition.